Zacchaeus’ Encounter with Jesus (Luke 19:1–10): An Embodiment of the Paschal Mystery - Luke Macnamara (The Biblical Annals)
Scholars have overlooked the significance of Zacchaeus’ movements in Luke 19:1–10. They are generally understood as a means of circumventing the crowd, a demonstration of his eagerness, an expression of his desire to see Jesus from a safe distance, or as a humorous scene. However, the captivating details of his ascent and descent from the tree call for a more satisfying explanation. The characterization of the rich toll collector carries pejorative overtones but afterwards he is counted among the lost who are saved. This transformation occurs through his participation in Jesus’ paschal mystery as represented by his climbing and coming down the tree.